Use of dexamethasone, remdesivir, convalescent plasma and prone positioning in the treatment of severe COVID-19 infection in pregnancy: A case report - Jennifer Jacobson; Kathleen Antony; Michael Beninati; William Alward; Kara K. Hoppe (Elsevier, 2021)
Severe infection with COVID-19 virus in pregnancy offers unique management challenges for the obstetrician and critical care specialist. We report the case of a woman at 26 weeks of gestation with acute respiratory distress syndrome secondary to COVID-19 infection treated with dexamethasone, remdesivir, convalescent plasma and mechanical ventilation. Cesarean delivery was performed at 29 weeks due to worsening maternal status. This case offers insight into the assessment and successful use of treatment strategies, including dexamethasone, remdesivir, convalescent plasma, early prone positioning, conservative fluid management, permissive hypoxia and low tidal volume parameters with ventilator support for pregnancies affected by severe COVID-19 infection.